2018
DOI: 10.17759/exppsy.2018110103
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of metacognitive determinants of management activity in the process of professionalization

Abstract: The study is devoted to the research of identification of characteristics and patterns of development of metacognitive processes and personal qualities of management activity during professionalization. Hypothesis of the existence of a direct connection between the level of professionalization of the subject and the degree of coherence of the structural organization of the main metacognitive parameters was verified in this study. Using diagnostic and experimental techniques of the study of metacognitive proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Interesting are the studies of A.V. Karpov, in which it is indicated that reflexivity as a property of the psyche is associated with the development of neuroticism and anxiety, so the higher a person has developed reflexivity, the higher the level of anxiety and neuroticism (Karpov, 2004). It was also established that pronounced self-observation can slow down human activity, reduce productivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interesting are the studies of A.V. Karpov, in which it is indicated that reflexivity as a property of the psyche is associated with the development of neuroticism and anxiety, so the higher a person has developed reflexivity, the higher the level of anxiety and neuroticism (Karpov, 2004). It was also established that pronounced self-observation can slow down human activity, reduce productivity.…”
Section: Resultsmentioning
confidence: 99%
“…A.V. Karpov, in turn, defined reflection as one of the main aspects of mental reality and proposed to divide it into three components: reflexivity, reflexive ability, and reflection itself (Karpov, 2004). Reflexivity is an individual mental property that is inherent in every person but at different levels of development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main ones, according to the classification of A.V. Karpov, are the following: -The ability to goal setting; -ability to predict; -ability to plan; -ability to make management decisions; -communication skills; -motivating abilities; -abilities of control [15].…”
Section: Main Text Theoretical Partmentioning
confidence: 99%
“…Currently, research on the formation of various meta-qualities and personality processes is being actively conducted (Karpov & Karpov, 2016;Karpov et al, 2017Karpov et al, , 2018. Creativity, personality's regulatory abilities (Karpov, 2013), self-organization and modeling (Klimontova, 2009), reflection of professional activity (Karpov, 2015;Shadrikov, 2013;Karpov & Klimontova, 2016;Shadrikov & Kurginyan, 2015) have been studied.…”
mentioning
confidence: 99%